1985
DOI: 10.1136/ard.44.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytes bearing Fc gamma receptors in rheumatoid arthritis. III. Immunoregulatory function associated with Facb rosette-forming cells.

Abstract: SUMMARY A subpopulation of mononuclear cells (PBMNC) that express Fc receptors with specificity for the Cy2 region of IgG may be detected by rosette formation with calf erythrocytes coated with the Facb fragmenit of rabbit IgG. These Facb-R' cells are found in increased numbers in the peripheral blood of patients with rheumatoid arthritis (RA). Studies have been carried out to identify the functional properties of these cells in healthy and rheumatoid subjects. Facb-R+ cells were shown to lack both natural kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Previous data have suggested that the major function of Facb-R+ cells is as accessory cells in antibody production. 6 The increase noted in Facb-R' cell numbers after immunisation may therefore have functional significance. The effective induction of an immune response to specific antigen requires an adequate supply of accessory cells presenting antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous data have suggested that the major function of Facb-R+ cells is as accessory cells in antibody production. 6 The increase noted in Facb-R' cell numbers after immunisation may therefore have functional significance. The effective induction of an immune response to specific antigen requires an adequate supply of accessory cells presenting antigens.…”
Section: Discussionmentioning
confidence: 99%
“…lymphocytes but that they express certain monocyte related markers and class II MHC antigens.5 Functionally, Facb-R+ cells are non-phagocytic4 and lack cytotoxic activity but act as regulatory cells in pokeweed mitogen driven IgG synthesis. 6 The factors which promote the increase in Facb-R+ cells in rheumatoid peripheral blood are unknown. Experiments in mice have shown that splenic Facb-R+ cells increase in number after secondary but not primary immunisation with a specific antigen, sheep erythrocytes.7 In view of this, numbers of circulating Facb-R+ cells have been monitored in healthy volunteers undergoing immunisation procedures and in cultures of PBMNC stimulated in vitro with specific antigen.…”
Section: Several Authors Have Demonstrated An Increased Expression Ofmentioning
confidence: 99%